Antenatal corticosteroids and perinatal outcome in late fetal growth restriction: analysis of prospective cohort. (1st February 2023) - Familiari, A.; Napolitano, R.; Visser, G. H. A.; Lees, C.; Wolf, H.; Prefumo, F.; ,
ABSTRACT: Objective: To evaluate the role of antenatal administration of corticosteroids for fetal lung maturation on the short‐term perinatal outcome of pregnancy complicated by late fetal growth restriction (FGR). Methods: This cohort study was a secondary analysis of a multicenter prospective observational study, the TRUFFLE‐2 feasibility study, conducted between 2017 and 2018 in 33 European perinatal centers. The study included women with a singleton pregnancy from 32 + 0 to 36 + 6 weeks of gestation with a fetus considered at risk for FGR, defined as estimated fetal weight (EFW) and/or fetal abdominal circumference < 10 th percentile, or umbilicocerebral ratio (UCR) ≥ 95 th percentile or a drop of more than 40 percentile points in abdominal circumference measurement from the 20‐week scan. For the purposes of the current study, we identified women who received a single course of steroids to improve fetal lung maturation before delivery. Each exposed pregnancy was matched with one that did not receive antenatal corticosteroids (ACS) (control), based on gestational age at delivery and birth weight. The primary adverse outcome was a composite of abnormal condition at birth, major neonatal morbidity or perinatal death. Results: A total of 86 pregnancies that received ACS were matched to 86 controls. The two groups were similar with respect to gestational age (33.1 vs 33.3 weeks), EFW (1673 vs 1634 g) and UCR (0.68 vs 0.62) at inclusion, and gestational age at delivery (35.5 vs 35.9 weeks) and birth weight (1925 vs 1948 g). No significant differences were observed between the exposed and non‐exposed groups in the incidence of composite adverse outcome (28% vs 24%; P  = 0.73) or any of its elements. Conclusion: The present data do not show a beneficial effect of steroids on short‐term outcome of fetuses with late FGR. © 2023 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.